Staphylococcus aureus NrdH Redoxin Is a Reductant of the Class Ib Ribonucleotide Reductase - Rabinovitch, Inbal (American Society for Microbiology (ASM), 2010)
Staphylococci contain a class Ib NrdEF ribonucleotide reductase (RNR) that is responsible, under aerobic conditions, for the synthesis of deoxyribonucleotide precursors for DNA synthesis and repair. The genes encoding that RNR are contained in an operon consisting of three genes, nrdIEF, whereas many other class Ib RNR operons contain a fourth gene, nrdH, that determines a thiol redoxin protein, NrdH. We identified a 77-amino-acid open reading frame in Staphylococcus aureus that resembles NrdH proteins. However, S. aureus NrdH differs significantly from the canonical NrdH both in its redox-active site, C-P-P-C instead of C-M/V-Q-C, and in the absence of the C-terminal [WF]SGFRP[DE] structural motif. We show that S. aureus NrdH is a thiol redox protein. It is not essential for aerobic or anaerobic growth and appears to have a marginal role in protection against oxidative stress. In vitro, S. aureus NrdH was found to be an efficient reductant of disulfide bonds in low-molecular-weight substrates and proteins using dithiothreitol as the source of reducing power and an effective reductant for the homologous class Ib RNR employing thioredoxin reductase and NADPH as the source of the reducing power. Its ability to reduce NrdEF is comparable to that of thioredoxin-thioredoxin reductase. Hence, S. aureus contains two alternative thiol redox proteins, NrdH and thioredoxin, with both proteins being able to function in vitro with thioredoxin reductase as the immediate hydrogen donors for the class Ib RNR. It remains to be clarified under which in vivo physiological conditions the two systems are used.